Systemic Inflammation after Third Molar Removal: A Case-Control Study. (December 2017) - Graziani, F.; D'Aiuto, F.; Gennai, S.; Petrini, M.; Nisi, M.; Cirigliano, N.; Landini, L.; Bruno, R.M.; Taddei, S.; Ghiadoni, L.
Third molar extraction is one of the most frequent interventions in dentistry. Nevertheless, there is scarce evidence on the host response of individuals with impacted or semi-impacted third molars and the possible effects of surgical removal. A case-control study of 40 patients was designed to evaluate 1) the differences in biomarkers of systemic inflammation, vascular function, and metabolism (high-sensitive C-reactive protein, lipids, fibrinogen, oxidative stress, and endothelial function analysis) and 2) the acute and short-term effects of surgical removal in patients with bilateral impacted or semi-impacted third molars compared to controls with no third molars. Patients undergoing third molar extraction exhibited greater levels of systemic inflammation, oxidative stress, and triglycerides than controls. Raised white blood cell counts as well as peaks of serum levels of C-reactive protein and fibrinogen were noticed in the first postoperative week. Three months after the extraction, all markers returned to baseline values. Malondialdehyde, an indicator of oxidative stress indicator, was significantly reduced after third molar removal. Semi-impacted or impacted third molars are associated with higher systemic inflammation, and their removal may represent a useful human model to study acute inflammation and determine beneficial systemic effects (ClinicalTrials.gov NCT03048175).